A dynamic long-term approach to internationalization: Spanish publishing firms’ expansion and emigrants in Mexico (1939–1977) - Moschieri, Caterina; Fernandez Moya, Maria (Springer Nature, 2022)
This study examines how firms with scarce market and non-market resources can succeed in internationalizing, even in a host country that lacks trade and diplomatic relationships with the firms’ home country. With a hand-collected, historical database of the Spanish publishing industry’s investments in Mexico over the 20th century, we find that in a context of suspension of bilateral trade agreements and diplomatic relationships between Spain and Mexico, Spanish publishing firms leveraged Spanish emigrants to internationalize in the Mexican market, initially through exports, then through distribution and local commercial subsidiaries, and finally through local production. Spanish publishers progressively used emigrants to develop social and cultural support, to help establish formal and informal rules, procedures, and norms of institutions and to lobby in Mexico. Combining historical and inductive analyses, we offer a novel perspective on firms’ internationalization through a changing use of emigrants to endogenize the cultural, trade, and political distance between the home and the host country, and we develop new theoretical insights on the social, cultural, and political embeddedness of firms.
Keywords: 53 Ciencias Económicas::5311 Organización y dirección de empresas; ODS 9 - Industria, innovación e infraestructura; ODS 17 - Alianzas para lograr los objetivos